Knowledge, attitudes and practices of neonatal staff concerning neonatal pain management - Sizakele L.T. Khoza; A. A. Tjale (AOSIS, 2014)
Background: Neonatal pain management has received increasing attention over the past four decades. Research into the effects of neonatal pain emphasises the professional, ethical and moral obligations of staff to manage pain for positive patient outcomes. However, evaluation studies continuously report evidence of inadequate neonate pain management and a gap between theory and practice. Objective: This study reviewed current practice in neonatal pain management to describe the knowledge, attitudes and practices of nurses and doctors regarding pain management for neonates in two academic hospitals. Method: A non-experimental, prospective quantitative survey, the modified Infant Pain Questionnaire, was used to collect data from 150 nurses and doctors working in the neonatal wards of two academic hospitals in central Gauteng. Results: The response rate was 35.33% (n = 53), most respondents being professional nurses (88.68%; n = 47) working in neonatal intensive care units (80.77%; n = 42); 24 (45.28%) had less than 5 years' and 29 respondents 6 or more years' working experience in neonatal care. A review of pain management in the study setting indicated a preference for pharmacological interventions to relieve moderate to severe pain. An association (p < 0.05) was found between pain ratings on 5 procedures and frequency of administration of pharmacological pain management. Two-thirds of respondents (64%) reported that there were no pain management guidelines in the neonatal wards in which they worked. Conclusion: The interventions to manage moderate neonatal pain are in line with international guidelines. However, neonatal pain management may not occur systematically based on prior assessment of neonatal pain, choice of most appropriate intervention and evaluation. This study recommends implementation of a guideline to standardise practice and ensure consistent and adequate pain management in neonates.